2001
DOI: 10.1007/s00232-001-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptors Control K + Secretion in Inner Ear Strial Marginal Cells

Abstract: K+ secretion in strial marginal cells (SMC) of stria vascularis (SV) is stimulated by beta1-adrenergic receptors. The aim of the present study was to determine, whether SMC from the gerbil inner ear contain muscarinic receptors that inhibit K+ secretion. Receptors were identified with pharmacological tools in functional studies where K+ secretion was monitored as transepithelial current (Isc). The cytosolic Ca2+ concentration ([Ca2+]i) was measured as fluo-4 fluorescence and cAMP production with a colorimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…1 C ) or when the nerve trunk was included with the spiral ganglion (supplemental Fig. 1, available at www.jneurosci.org as supplemental material), an M 3 band was present: M 3 receptors have been detected, by RT-PCR, in microdissected stria vascularis (Wangemann et al, 2001) and may also be expressed in the nerve-root nucleus and/or parts of the cochlear nucleus that are present when the modiolus is included (Merchan et al, 1988). All PCR bands were sequenced to verify the identity of the amplicons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 C ) or when the nerve trunk was included with the spiral ganglion (supplemental Fig. 1, available at www.jneurosci.org as supplemental material), an M 3 band was present: M 3 receptors have been detected, by RT-PCR, in microdissected stria vascularis (Wangemann et al, 2001) and may also be expressed in the nerve-root nucleus and/or parts of the cochlear nucleus that are present when the modiolus is included (Merchan et al, 1988). All PCR bands were sequenced to verify the identity of the amplicons.…”
Section: Resultsmentioning
confidence: 99%
“…Previous RT-PCR study in gerbil reported M 3 expression in microdissected stria vascularis (Wangemann et al, 2001). Transcripts for M 1 , M 3 , and M 5 (but not M 2 or M 4 ) were amplified from whole mouse cochleas (Drescher et al, 1992), and, in rats and guinea pigs, M 3 transcripts were found in microdissected organ of Corti and spiral ganglion (Safiedine et al, 1996).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the rate of K ϩ secretion is increased by ␤ 1 -adrenergic receptors via cAMP-dependent stimulation of the KCNQ1/KCNE1 K ϩ channel (258,259,309,310). Conversely, muscarinic and purinergic receptors suppress K ϩ secretion (307). Purinergic P2Y 4 receptors decrease currents through the KCNQ1/KCNE1 K ϩ channel via protein kinase C (160,166).…”
Section: K ϩ Cycling In the Inner Earmentioning
confidence: 98%
“…P2X 2 receptors are widely distributed in the inner ear, but not in the stria vascularis (Housley et al, 1998;Housley et al, 1999), and it has been shown that K + secretion is regulated via P2Y 4 receptors in the apical membrane of the marginal cells residing in the stria vascularis (Marcus et al, 2005). Moreover, P2Y 2 (Sage and Marcus, 2002), 1-adrenergic, and muscarinic receptors (Wangemann et al, 2001) have been reported at the basolateral membrane, and it is believed that the sources of agonists for these receptors are the strial marginal cells (White et al, 1995) and the organ of Corti (Wangemann, 1996).…”
Section: Introductionmentioning
confidence: 98%